Забезпечення автоматизації внутрішнього документообігу ЛКП за даними системи Alfresco - Багрій, Максим; Сєров, Юрій (Видавництво Львівської політехніки, 2016)
This article describes the current state of internal workflow automation companies. Object is Lviv municipal enterprise "City center of information technology". This article describes how to create internal documents with the help of Alfresco.
Keywords: Alfresco; внутрішній документообіг; система управління документами; організація електронного документообігу